Galectin-3 Level Insera Patients with Bladder Cancer in Babylon Province - HibaResheed Behayaa; Mufeed Jalil Ewadh; Ahmed Turki Obaid (Institute of Medico-legal Publications Pvt Ltd, 2021)
For the assessment of Galectin-3 leveland toinvestigate the possible relation of Galectin-3 with age, genderand different stage and grade of bladder cancer in Babylon province. Galectin-3 was measured in two hundredsubjects; 100 diagnosed with bladder cancer and 100 healthy subjectswere registered in this revision.Theage of patients and control ranged between (38-79) years.The level of Galectin-3was assessed in serum byenzyme- linked immunosorbent assay (ELISA)technique.Serum levels of Galectin-3displayed a significantincrease in bladder cancer group associated with control group (p<0.01). Amongbladder cancer patients inBabylon province, increase Galectin-3 concentration indicate the significant relationshipwithbladder cancer.